Contesting Corporate Social Responsibility: Community Agency, Hegemony, and Ecological Justice in Berau’s Coal Mining Region (International Forum of Researchers and Lecturers, 2025)
This study examines the practice of Corporate Social Responsibility (CSR) by PT Berau Coal in Berau Regency, East Kalimantan, focusing on dynamics of hegemony, meaning-making, and ecological justice. Berau, as one of Indonesia’s major coal-producing regions, reflects a development paradox: while the company has gained recognition for its economic contributions and CSR programs, local communities continue to experience environmental degradation, land dispossession, and limited participation. The research employs a qualitative case study approach using in-depth interviews, focus group discussions, observations, and document analysis in four mining-affected villages. The analysis is guided by Gramscian hegemony, Berger and Luckmann’s social constructivism, and critical political ecology. Findings indicate that CSR primarily functions as a hegemonic strategy that normalizes extractivism through tokenistic participation, corporate-led development narratives, and community dependence on company resources. Yet, local actors are not passive. Youth groups, women’s cooperatives, and traditional leaders emerge as critical voices who negotiate CSR agendas, reinterpret corporate narratives, and, in some cases, reject projects that fail to meet community needs—such as the case of the Jalan Usaha Tani project in Gunung Tabur. From a political ecology perspective, CSR practices remain confined to administrative compliance and symbolic environmental gestures, while structural ecological injustices persist. The study recommends transforming CSR into a participatory, transparent, and community-centered governance model by strengthening multi-stakeholder platforms, institutionalizing co-design processes, and recognizing local ecological knowledge.